Meningkatkan Hasil Belajar Peserta Didik dengan Modul Pembelajaran Berbasis Problem Based Learning (PBL) - Widayanti, Yesika (Jurnal Pendidikan Ekonomi Undiksha, 2020)
The low critical thinking skills of students at SMAN 1 Driyorejo have an impact on the low learning outcomes and the quality of education at the school. To overcome this need a development of teaching materials that require students to think critically and improve learning outcomes. This study was designed to meet the needs of learning media with the aim of describing the module development process according to Thiagarajan, analyzing the feasibility of the modules developed, describing student learning outcomes, and describing differences in student learning outcomes. Research type of research and development are assessed by material experts, linguists, evaluation experts, and graphic experts. Using the 4D model from Thiagarajan. The research procedure includes 3 phases, define, design, and develop. Instruments of product validity were obtained from material experts, linguists, evaluation experts and graphic experts. The results of this study show that the development of PBL-based modules is considered "Decent" based on the average validation of experts, the existence of PBL-based modules can improve student learning outcomes and is strengthened by the difference between learning outcomes of students who use PBL modules with the learning outcomes of students who do not use PBL modules.